2014
DOI: 10.1016/j.pharep.2014.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Association between chemotherapy and plasma adipokines in patients with colorectal cancer

Abstract: The results of the present study are relevant because we found that chemotherapy in colorectal cancer patients, in addition to its beneficial clinical impact on the course of disease, positively affects cytokine production and release (increases the anti-inflammatory adiponectin and decreases visfatin and resistin, which are proangiogenic and promote cancer cell proliferation). The restoration of adequate adipose tissue function is essential for patients to achieve a good survival prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
3

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
1
9
0
3
Order By: Relevance
“…Although beyond the scope of this study, Karapanagiotou et al (62) revealed a lack of prognostic value for the assessed adipokines in patients with advanced NSCLC. Concordant with these findings, a recent study by Slomian et al (63) revealed a significant increase in circulating levels of leptin and adiponectin in a cohort of patients with advanced colorectal cancer who required palliative chemotherapy.…”
Section: Hgf Pg/mlsupporting
confidence: 62%
“…Although beyond the scope of this study, Karapanagiotou et al (62) revealed a lack of prognostic value for the assessed adipokines in patients with advanced NSCLC. Concordant with these findings, a recent study by Slomian et al (63) revealed a significant increase in circulating levels of leptin and adiponectin in a cohort of patients with advanced colorectal cancer who required palliative chemotherapy.…”
Section: Hgf Pg/mlsupporting
confidence: 62%
“…Indeed, in vitro , visfatin leads to increased cancer cell survival and migration [29], the preferentially stimulated proliferation of HCC cells [18], and the increased viability of the cancer cells by inducing antioxidative activity [30]. In vivo , the visfatin levels decreased significantly after chemotherapy [31]. On the basis of previous studies and our results, visfatin could be a potential therapeutic target of HCC.…”
Section: Discussionmentioning
confidence: 57%
“…Visfatin, which is secreted by visceral fat, is a new adipokine that is structurally identical to pre-B-cell colony-enhancing factor (PBEF) and exhibits nicotinamide phosphoribosyltransferase (NAMPT) enzymatic activity (Dalamaga et al, 2012;Tulubas et al, 2013) Elevated circulating levels of visfatin have been found in patients with metabolic disorders, such as diabetes mellitus, obesity or metabolic syndrome (MS), which might be related to the development of MS-related cancers (Słomian et al, 2014) So, in this study we aimed to evaluate the levels of (Adiponectin, Resistin and Visfatin) in pre-malignant and malignant colorectal lesions for early detection to understand the possible role of adipocytokines in relation to disease progression and early detection of colorectal cancer.…”
Section: Circulating Levels Of Adipocytokines As Potential Biomarkersmentioning
confidence: 99%